Fiber Derived Microbial Metabolites Prevent Acute Kidney Injury Through G-Protein Coupled Receptors and HDAC Inhibition - Liu, Yunzi; Li, Yan J.; Loh, Yik W.; Singer, Julian; Zhu, Weiping; Macia, Laurence; Mackay, Charles R.; Wang, Weiming; Chadban, Steven J.; Wu, Huiling (Frontiers in Cell and Developmental Biology, 2021)
Short-chain fatty acids (SCFA) derived from gut microbial fermentation of fiber have been shown to exert anti-inflammatory and immune-modulatory properties in acute kidney injury (AKI). However the direct mechanistic link between SCFAs, diet and the gut microbiome is yet to be established. Using the murine model of folic-acid nephropathy (FAN), we examined the effect of dietary fiber on development of AKI (day 2) and subsequent chronic kidney disease (CKD) (day 28). FAN was induced in wild-type and knockout mice lacking G protein–coupled receptors GPR41, GPR43 or GPR109A. Mice were randomised to high-fiber or normal-chow diets, or SCFAs in drinking water. We used 16S rRNA sequencing to assess the gut microbiome and 1H-NMR spectroscopy for metabolic profiles. Mice fed high-fiber were partially protected against development of AKI and subsequent CKD, exhibiting better kidney function throughout, less tubular injury at day 2 and less interstitial fibrosis and chronic inflammation at day 28 versus controls. Fiber modified the gut microbiome and alleviated dysbiosis induced by AKI, promoting expansion of SCFA-producing bacteria Bifidobacterium and Prevotella, which increased fecal and serum SCFA concentrations. SCFA treatment achieved similar protection, but not in the absence of GPR41 or GPR109A. Histone deacetylase activity (HDAC) was inhibited in kidneys of high-fiber fed mice. We conclude that dietary manipulation of the gut microbiome protects against AKI and subsequent CKD, mediated by HDAC inhibition and activation of GPR41 and GPR109A by SCFAs. This study highlights the potential of the gut microbiome as a modifiable target in the prevention of AKI.